1886 Md. Laws 602 - (:unkn) unknown (My University, 1886)
Ch. 375: Prohibited carrying, concealed or openly with intent or purpose of injuring another, any pistol, dirk-knife, Bowie-knife, slung-shot, Billy, sandclub, metal knuckles, razor, or any other dangerous or deadly weapon whatsoever.
Keywords: CARRY - INTENT TO COMMIT CRIME